Biotransformation of caffeic acid into a promising biologically active metabolite by Candida albicans isolate CI-24 - Raghda A. Singab; Ahmed M. Elissawy; Walid Faisal Elkhatib; Mahmoud A. Yassien; Nadia A. Hassouna (Ain Shams University, 2018)
In this study, a total number of 92 clinical isolates of Candida species was used to test their ability to transform caffeic acid using the two-stage fermentation protocol. The success of the biotransformation process was confirmed by TLC autography method and nuclear magnetic resonance analysis. The obtained chromatograms showed that 7 isolates could perform caffeic acid biotransformation. The biological activities (antibacterial, antifungal, antiviral, and cytotoxic activities) of the extracts of the selected isolates were determined. According to the obtained results, the Candida isolate CI-24 had the most promising biotransformation ability. The methanolic extract of the respective isolate showed a promising anticancer activity against Caco-2 cell line and a potential antibacterial activity against Staphylococcus aureus ATCC 25923. The isolate was genetically identified as Candida albicans (Accession number MH356583) using 28S rRNA sequencing. As determined by NMR and LC-MS analysis, caffeic acid was transformed by Candida albicans strain CI-24 into para-hydroxybenzoic acid.